UV-B irradiation enhances the production of unique mycosporine-like amino acids and carotenoids in the subaerial cyanobacterium Pseudanabaena sp. CCNU1. Issue 3 (3rd July 2021) - Boucar, Mamadou Chetima Maina; Shen, Li-Qin; Wang, Kai; Zhang, Zhong-Chun; Qiu, Bao-Sheng
ABSTRACT: The harmful effects of ultraviolet (UV) radiation have increased the demand for new sources of UV photoprotectants to develop cosmetic and skin care products. In this study, a filamentous cyanobacterial strain was isolated from the topsoil collected in an arid and exposed region in Chetimari, Niger. On the basis of 16S rDNA sequences, the isolated strain was identified as Pseudanabaena sp. CCNU1. UV-B treatment of Pseudanabaena sp. CCNU1 significantly enhanced the production of active photoprotectants, including UV-absorbing mycosporine-like amino acids (MAAs) and carotenoids. UV-B irradiation mainly induced the production of one MAA, identified as palythine-serine. The palythine-serine content was as high as 16 mg g −1 dry weight after a 4-day UV-B treatment. Eight carotenoids were detected in the methanol extracts of UV-B-treated Pseudanabaena sp. CCNU1: β-carotene, echinenone, canthaxanthin, zeaxanthin, synechoxanthin, and three myxoxanthophyll derivatives. With the exception of β-carotene and echinenone, these carotenoids were positively correlated with the UV-B treatment duration. Thus, Pseudanabaena sp. CCNU1 was identified as a unique organism that produces a considerable abundance of palythine-serine as well as carotenoids to protect against UV-B radiation. Pseudanabaena sp. CCNU1 may be useful as a producer of UV photoprotectants, although the genetic basis of the relevant biosynthetic pathways remains to be precisely characterized in the future.